Primary intramedullary primitive neuroectodermal tumor: A case report and review of the literature - Wang, Guoqing (Medicine (Baltimore), 2017)
RATIONALE: Primary spinal primitive neuroectodermal tumors (PNETs) are highly malignant tumors, which are extremely rare entities and primary intramedullary PNETs are extremely rare. Till now, only 24 cases of primary intramedullary PNET have been reported. PATIENT CONCERNS: A 26-year-old male presented with progressive low back and lower limb pain for 1 month. DIAGNOSES: Based on MRI and histopathological findings, he was diagnosed with primary intramedullary PNET. INTERVENTIONS: The patient was treated two times with microsurgical resections. OUTCOMES: Follow-up visit at 14 months after the first surgery showed that the patient is neurologically intact and free of disease. LESSONS: PNETs should be considered in the differential diagnosis of an intramedullary spinal cord tumor manifesting as progressive neurological deterioration.